Birds are valuable: the case of vagrants. Issue 1 (2nd January 2020) - Callaghan, Corey T.; Benson, Ian; Major, Richard E.; Martin, John M.; Longden, Thomas; Kingsford, Richard T.
ABSTRACT: Biodiversity values need to be appropriately quantified and thence incorporated in future land development decisions. We assessed the economic and conservation-fundraising potential of vagrant Aleutian Terns in New South Wales, Australia. We found that an estimated 375–581 birdwatchers travelled far (580 ± 522 km [mean ± SD]) and reacted quickly (22% of visits were within the first week and 47% within the first two weeks) to see Aleutian Terns in an area where they had never been seen. We estimated that the total expenditure of these birdwatchers ranged from ∼ $199, 000–$363, 000 AUD and we further estimated that birdwatchers would have been cumulatively willing to donate upwards of $30, 000 AUD to a non-governmental conservation organisation in order to have viewed the terns. These results suggest that birdwatchers highly value vagrant birdwatching and conservation campaign potential should be explored in future long-staying vagrant bird occurrences.